Pengaruh prenatal yoga terhadap kualitas tidur pada ibu hamil trimester III - Atik Ismiyati; Zulfikar Husni Faruq (PUINOVAKESMAS, 2020)
The effect of prenatal yoga on sleep quality in third trimester pregnant women. Background: Pregnancy entering the third trimester occurs physical and psychological changes. This condition causes pregnant women to experience complex complaints, one of which is disturbance when sleeping. By doing prenatal yoga is useful for overcoming sleep difficulties so that it can improve the health of the mother and the fetus. Research Objectives: To determine the effect of prenatal yoga on sleep quality of third trimester pregnant women at PMB Poltekkes, Yogyakarta Midwifery Department. Methods: This type of research is pre-experimental with a one group pre-test-post-test design. The population in this study were pregnant women with gestational age above 28 weeks with a total of 32 pregnant women. The sampling technique uses total sampling. The research instrument used PSQI, data analysis used paired sample t-test. Results: The results of data analysis showed that before implementing prenatal yoga, the mean value decreased from 9.28 to 6.44. Based on statistical tests using paired sample t-test with the help of SPSS showed p = 0.000; where the p-value <0.05, which means that Ha is accepted. Conclusion: There is an effect of prenatal yoga on the sleep quality of pregnant women in the third trimester.